Efeitos da hibridização no pseudogap em um modelo de Hubbard d-p - Lalis, Diovana de Mello (2019)
In this paper, we investigate the effects of hybridization with different symmetries on the normal and superconducting properties of a Hubbard d-p model. The Hubbard d-p model is a variation of the model proposed by Hubbard to describe strongly correlated electron systems. This model was proposed to describe materials with different types of bands. A narrow band associated with poorly moving electrons and a wide band. Mixing these two bands can generate interesting behaviors for the system. Variation of external parameters, such as pressure or doping, can lead the system from a metallic state to an insulating state, or even to a superconducting state. Hybridization between bands depends on parameters such as external pressure. The symmetry of hybridization is also important when analyzing the normal and superconducting properties of the system. In this paper, we will consider an isotropic symmetry, ie s symmetry, s extended-wave symmetry, and dp wave symmetry. The objective is to study how these different symmetries influence the behavior of the normal state and the superconducting state of the model. The model is studied using the Green’s function technique together with an n-pole approximation to the Green functions. The approximation of n-poles allows us to investigate the behavior of a pseudogap in the density of states, as observed in cuprate superconductors. Cuprates show an anomalous behavior in the normal phase where there is a pseudogap that can be observed in the density of states. Pseudogap has been heavily investigated for the purpose of trying to understand the mechanisms of superconductivity in these systems. The results show that pseudogap depends on the symmetry of hybridization, being favored by symmetry dp and disadvantaged by symmetry s-extended. This result can be understood by analyzing the spin-spin correlation function, which can be associated with antiferromagnetic correlations. A investigation of the Fermi surface topology was also performed, showing the occurrence of a Lifshitz transition when the system enters a regime of strong correlations. It was observed that the Lifshitz transition depends on different model parameters such as Coulomb interaction and hybridization, and is also influenced by the symmetry of hybridization.